Evaluating and Validating an Instrument for Digital Government Ambidexterity - NDLOVU N.; OCHARA N.M.; MARTIN R.L. (Communications of International Proceedings, 2021)
Regarding the scantiness of research on digital government ambidexterity, the current paper further offers to enhance our understanding in the field of digital technologies through availing processes used in evaluating the data collection instrument. The thrust of this research was to develop a questionnaire for measuring citizens’ evaluation of exploitative incremental digital innovation and explorative radical digital innovation in the context of municipalities from developing countries. We further sought to determine information usability, information readability, information relevance, information trustworthiness and information completeness. Content validation was conducted, and the questionnaire was subjected to pilot testing. Cronbach’s alpha test was also conducted to assess reliability of the instrument. The content validation was considered by experts to be good, except for an item on digital government policy implementation. This item was deemed misplaced, and it was eventually removed from the instrument. The exploratory factor analysis was also conducted, and of the 46 measurement items 1 item was excluded. The partial least squares structural equation modelling of the resultant 45 item questionnaire confirmed the 11initial domains established. The goodness of fit for the model was established through the standardised root mean square residual. The structural model was tested for its predictive power and significance of the proposed relationships.
Keywords: Digital Government Ambidexterity; Public Value; Questionnaire; Evaluation